PENGARUH RASIO LIKUIDITAS DAN RASIO AKTIVITAS TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Eprilia, Intan; Siregar, Dian Lestari (EDUTECH CONSULTANT, 2020)
This Research aims to determine the influence of current ratio and total asset turnover of the company's return on asset manufacturing of food and beverage sub sectors listed on the Indonesia Stock Exchange period 2014-2018. The independent variables used in this research are current ratio and total asset turnover. The dependent variable used in this study is return on asset. The study population is 24 food and beverage companies. Sampling in this study using purposive sampling method is with predefined criteria so that acquired 11 companies that meet the criteria. The type of data used is secondary data, and the data analysis model used is multiple regression analysis. The data processing is done by using the help of the program statistics SPSS version 25 for Windows. Results in this study showed that: (1) Current ratio affects return on asset, (2) Total asset turnover has no effect on return on asset, (3) simultaneously, Current ratio and Total asset turnover affect return on Asset.